Non-Native English Speaker Teacher Narration of Nativism - Muhammad Iqbal Ripo Putra; Citra Iswara; Dedi Irwan * (Universitas Tanjungpura, 2021)
The 21st century ELT world is trying to migrate into the more relevant notion of international English. This notion, supposedly, supports every English speaker of a different nation, background, and culture. However, the public preference in native speaker is still apparent. This study is aimed to explore one non-native English speaker teacher’s experiences in teaching English along with a native English speaker teacher. This study employed narrative inquiry, the data gathered by interviews, and document analysis. The non-native English speaker teacher experiences several discriminations in the form of job division, job requirements, and even the wage difference. The public preference for native English speaker teachers is still apparent, looking at the growth of schools with native-speaker teachers.